Drought stress responses in tolerant and sensitive varieties of black pepper (Piper nigrum Linn.) - Vijayakumari, K.; Puthur, Jos T. (Journal of Plantation Crops, 2014)
Stress responses towards drought was studied in drought tolerant (Panniyur 5) and sensitive (Panniyur 1) varieties of black pepper. On exposure to 15 days (incipient wilting) of drought, Panniyur 1 (P1) showed low RWC of leaves, highly reduced ψs and decrease in the capacity to synthesize sugars and proline as compared to Panniyur 5 (P5). These features indicate the reduced potential of P1 to tolerate long periods of drought as compared to P5. The malondialdehyde content was found to be significantly higher in P1 when compared to P5 during drought. The activity of antioxidant enzymes (guaiacol peroxidase and superoxide dismutase) were found to be low in P1 as compared to P5 at different stages of drought stress, indicating that P1 is comparatively less shielded than P5 from the deleterious effects of reactive oxygen species generated as a result of drought exposure. The photosystems and mitochondria of P1 were more sensitive to drought as compared to that of P5. The effective control of lipid peroxidation and better osmotic adjustments in cells of tolerant variety (P5) may be the prime factors for the increased tolerance of photosystem and mitochondrial systems towards drought stress.